Respostas

2014-07-15T19:33:49-03:00
{2x-y²=1 
{3x+y=4 

I.Isolar Y na 2°equação 
3x+y=4 
R:y=4-3x 

II.Substituir y na 1° equação 
2x-y²=1 
2x-(4-3x)²=1 
2x-(4-3x).(4-3x)-1=0 
2x-(16-12x-12x+9x²)-1=0 
2x-16+12x+12x-9x²-1=0 
-9x²+2x+12x+12x-16-1=0 
-9x²+26x-17=0 
a=-9 
b=26 
c=-17 
delta=b²-4.a.c 
delta=(26)²-4.(-9).(-17) 
delta=676-612 
delta=64 
x=-b±√delta 
_______ 
2.a 
x=-26±√64 
________ 
2.(-9) 
x=-26±8/-18 

x¹=-26+8/-18 x²=-26-8/-18 


x¹=-18/-18 x²=-34/-18 


x¹=1 x²=17/9 

III.volto em y=4-3x 
para x¹=1 para x²=17/9 
y¹=4-3x y²=4-3x 
y¹=4-3.1 y²=4/1-3/1.17/9 
y¹=4-3 y²=4/4-51/9 
y¹=1 y²=36-51/9 
y²=-15/9 
y²=-5/3 
S={1;17/9;1;5.3} 

Acho que é isso xP Espero ter ajudado ;)
2 5 2